Assessment Of Nutrient And Chlorophyll Content Variation In Leaves Of Neem (Azadirachta Indica A. Juss.) From Northern Provenances Of India (International Journal of Environmental Sciences, 2025)
Azadirachta indica A. Juss., is native to the Indian subcontinent and has enormous social, economic, and medicinal significance. Despite its widespread distribution, the chemical composition of its leaves varies greatly between regions according to agroclimate, especially with regard to the amount of chlorophyll and nutrients. This study analyzed data from diverse locations across northern India, covering eight districts in Uttar Pradesh (Gonda, Rampur, Aligarh, Badaun, Barabanki, Ambedkar Nagar, Banda, and Chitrakoot), along with sites from Uttarakhand (Haldwani, Ramnagar, Sitarganj), Punjab (Sangrur, Patiala), Rajasthan (Kota, Ajmer), Haryana (Panchkula, Ambala), and Delhi (Central Delhi, South Delhi). The investigation focused on two chlorophyll pigments and carotenoids (chlorophyll-a, chlorophyll-b, and carotenoids) and three essential macronutrients (potassium, phosphorus, and nitrogen). By examining ecological influences on the physiological parameters of Azadirachta indica, this work provides critical insights for its sustainable utilization in forestry, agriculture, and phytopharmaceutical development across different agroclimatic regions of northern India.